Innovative power-sharing model for buildings and energy communities. (July 2021) - Di Lorenzo, Gianfranco; Rotondo, Sara; Araneo, Rodolfo; Petrone, Giovanni; Martirano, Luigi
Abstract: The paper proposes an innovative power-sharing model, i.e., a power-system architecture for aggregation of users able to share the power produced by common generators and energy services. The model is suitable for both multi-tenant buildings and groups of multiple buildings and it is applicable for both existing and new buildings. It is scalable for larger systems and suitable for an easier integration with storage systems. The novel principle of the model is that the energy produced by common generators can be shared among the end-users in a unidirectional way, so that each user remains passive towards the distributor, except a single active user that assumes the role of balance node. This key feature allows for easily implementing the model in all the residential and tertiary multi-units buildings in full compliance with national regulations, with the adoption of power sharing contracts as well. This paper discusses the feasibility of the model through a dynamic Matlab/Simulink model, which is used to show its effectiveness in several case studies. The significance of this work consists of approaching the energy sharing in buildings with a completely new strategy, based on an innovative system architecture that can be effectively implemented. Highlights: Innovative democratic power-sharing model for building and energy communities. It allows for aggregation of users. It allows to share the power produced by common generators. Each user remains passive towards the distributor. The model can be implemented in all multi-units buildings.